Talking Communication Studies: Negotiating Power and Promise - Klaehn, Jeffery; Zollmann, Florian; Kahn, Marcus (Javnost-The Public, 2022)
Consensus regarding what becomes mainstream, popular, and commonplace within academia is subtly managed in accord with conformity of thought, contemporary popular ideas, and major assumptions/paradigms predominating fields, which in turn are comprised of hegemonic, ideological ideas, frameworks and arguments that are informed and bound by power. Power, professionalisation, and dominant ideological currents inform and legitimise paradigmatic ideas, which in turn influence perceptions and reception. This paper explores how Communication Studies have been impacted by dominant configurations of power and encourages debate on the extent to which ideological bias and ideological marginalisation are normative dimensions of Communication Studies.